The relationship between poverty and HIV/AIDS in Sudan / Salwa Muddthir Ismail - Ismail, Salwa Muddthir (2015)
This thesis investigates the complex and vicious circle of poverty and Human Immune Virus (HIV)/Acquired Immune Deficiency Syndromes (AIDS) in Sudan. The study focuses on selected dimensions of poverty that increase the risk and vulnerability to HIV/AIDS, which is pertinent as poverty can hamper mitigating efforts. The study adopted the livelihood, drive and structuration theories approach as the theoretical framework, to investigate the relationship between poverty and HIV/AIDS in Sudan. The study was conducted using a mixed method approach. Quantitative data from people living with HIV/AIDS was compiled using survey questionnaires while qualitative data gathered from Focus Group Discussions. The study also deployed data from the 2010 Sudan Household Health Survey. Data was analysed using structural equation modelling, discriminant analysis and Scissor-and-sort. In addition, T-tests and chi-squire tests were carried out to strengthen the descriptive findings. The findings brought out evidence that poverty and related factors were significant contributors to exposing the people in Sudan to HIV-risks. Furthermore, HIV epidemic forces people living with HIV/AIDS to utilise their savings for healthcare expenses, which then pushes them to borrow and sell their assets. The empirical evidence amassed also showed significant variations in coping strategies between men and women, with the latter being more vulnerable than the former to the impact of the disease, which is due to women’s low income, low level of education and hence their low ability to pay for children’s schooling and health care expenses. In addition, the results demonstrated that low education; low economic status and gender inequality significantly affects HIV- risk among poor men, while significantly increasing the risk of HIV infection among women in all segments of society. These variables coupled with social, cultural and traditional factors, place women in Sudan at a disadvantage. Hence, the study suggests that, women are more vulnerable than men to HIV due to poverty as well as social, cultural and structural factors. The results offer compelling evidence for the formulation of comprehensive approaches to HIV prevention that cut across all socio-economic strata of the community. In addition, there is need to target the drivers of transmission in specific groups, mainly most at risk populations. Thus, the key message to health care policy-makers is to extend efforts to strengthen prevention and treatment interventions without ignoring the vulnerability and its associated socio-economic factors. This study offers several contributions. Firstly, it provided qualitative and quantitative empirical evidence to establish the causal relationships between poverty and HIV/AIDS in Sudan. The results help fill a lacuna in understanding HIV/AIDS problems in Sudan specifically, and the developing countries generally, which can be used by policy-makers to formulate effective preventive strategies at the national and local levels. Secondly, the survey findings by gender provided important information about the variation in socio-economic background, and demographic variables and assessed the risk behaviours that exit between men and women in the context of vulnerability to HIV infection and coping strategies among infected people in Sudan. This information can be utilised to formulate effective preventive strategies that take account of socio-economic background of vulnerable groups Thirdly, the study used different data sets and a sound conceptual framework to generate a comprehensive set of conclusions establishing the link between socio-economic background and HIV/AIDS risks. Fourthly, and most interestingly, the study proposed a model, which can be deployed as a promising tool to identify the socio-economic factors that are likely to cause HIV-risk. Fifthly, the study provides significant empirical evidence of the importance of education in reducing the spread of HIV by avoiding HIV risk through using condoms, adherence to one non-infected partner, avoiding sexual contact with irregular partners and high-risk populations Finally, the study identified the impact of HIV/AIDS in Sudan, the results of which are hoped to be useful for researchers interested in strengthening their understanding of HIV/AIDS as not just a health problem but also a development problem.